Analisis Tentang Tujuan Pendidikan Agama Kristen (PAK) Dalam Matius 28:19-20 - Rinaldus Tanduklangi (PEADA': Jurnal Pendidikan Kristen, 2020)
The Gospel of Matthew is a part of the new covenant the presents the great commission of the Jesus. The great commission is the command of the Lord Jesus to the disciples and to all believers in all ages. The great commission becomes the foundation in carrying out educational actions for the world in which Jesus has provided instructions, methods and ways of implementing them. The great commission becomes the foundation of education especially Christian religious education. This paper aims to analyze theologically the objectives of Christian religious education based on Matthew 28: 19-20. In an effort to trace the intention used qualitative-descriptive research methods. The results obtained that the purpose of PAK based on Matthew 28: 19-20's exposure is to make disciples of all nations, baptize and teach them to do all the commands of the Jesus. Injl Matius merupakan salah satu bagian kitab perjanjian baru yang menyajikan amanat agung Tuhan Yesus. Amanat agung ialah perintah Tuhan Yesus bagi para murid dan kepada semua orang percaya di segala zaman. Amanat agung menjadi landasan dalam melaksanakan tindakan pendidikan bagi dunia yang di dalamnya Yesus telah memberikan petunjuk, metode dan cara pelaksanaannya. Amanat agung menjadi landasan  pendidikan khususnya pendidikan agama Kristen (PAK). Tulisan ini bertujuan untuk menganalasis secara teologis tujuan pendidikan agama kristen (PAK) berdasarkan Matius 28:19-20. Dalam upaya menelusuri maksud tersebut digunakan metode penelitian kualitatif-deskriptif. Hasil yang diperoleh bahwa tujuan PAK berdasarkan paparan Matius 28:19-20 ialah memuridkan segala bangsa, membaptis dan mengajar mereka melakukan segala perintah Tuhan Yesus.